The Effect of Community-Based Entrepreneurship Development Programs on Improving the Economic Welfare of Communities in Rural Areas - Hasmawati, Hasmawati; Winarti, Winarti; Jumriani, Jumriani; Arfah, Muhammad Isra Chikah; Jafar, Jafar (Celebes Journal of Community Services, 2024)
This study aims to systematically review the impact of community-based entrepreneurship development programs on the economic welfare of rural communities, identifying key success factors, contributions to economic welfare, and best practices from successful initiatives. A qualitative research design with a systematic review approach was employed, focusing on peer-reviewed journal articles, conference papers, and relevant reports published between 2018 and 2023. Data collection involved a comprehensive search of academic databases, and data analysis techniques included thematic analysis and meta-synthesis to identify common themes and patterns. The review revealed that successful community-based entrepreneurship programs are those that align with local context and culture, provide access to financial resources and effective training, foster strong social networks, and ensure sustainability and scalability. Programs tailored to the socio-cultural dynamics of rural communities showed higher engagement and acceptance. Access to microfinance and continuous capacity-building initiatives were critical for business growth and sustainability. Social capital and networks provided essential resources and support, while continuous support mechanisms and adaptability were vital for long-term success. These findings align with various economic, human capital, and social capital theories. The study offers valuable insights for policymakers and practitioners to design more effective community-based entrepreneurship programs. These programs can significantly improve rural economic welfare by integrating local context, financial support, training, and social networks. The findings also highlight the need for continuous support and adaptable program designs to sustain and scale entrepreneurship initiatives, contributing to sustainable and inclusive economic development in rural.